Analysis of the mother-father relations of adolescents who stayed at home during the pandemia process - Çelik, Melike Yavaş; Ayar, Duygu (Acta Scientiarum. Health Sciences, 2024)
This research has been planned in a descriptive way to examine the mother-father relationships of adolescents during the pandemic process. The data were collected with Personal Information Form and Adolescent-Mother, Father Relationship Inventory. T test, (ANOVA), Kruskal Wallis and Mann Whitney U test were used for analysis. The score average of the Mother, Father Relations Inventory filled out by adolescents for their mothers was 120.89 ± 21.68, and the average score of the Mother, Father Relations Inventory filled out by adolescents for their fathers was 136.65 ± 36.74. It was determined that the Adolescent-Mother, Father Relations Inventory scores for the mothers and fathers were statistically significant in terms of variables such as the mother-father relationship status before the pandemic, the effect of the pandemic on the mother-father relations, and family attitudes (p < 0.05). During the pandemic process, adolescents’ mother-father relationships are interrupted and there are problems in their mother-father relationships.